Draft Annual Plan Programme 2008-2009 Volume-II Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2008)
The Govt. of India have constituted the Port Management Board to administer and to create the necessary infrastructure facilities in the declared Ports of Andaman and Nicobar Islands in the pattern of smaller Major Ports like Tuticorin and New Mangalore. the function of the Board has been increased considerably consequent on taking over the administration and operational control of all 23 declared Ports of A&N Islands as notified vide GOI Notification No. GSR 468(E) dated 07.05.1996.
Andaman and Nicobar Administration, Planning Department